Potencialidad metalogénica de las unidades exo y endograníticas en el yacimiento S.M.W. de Fontao (Galicia,España) - Arribas, A.; Ovejero, G.; Gagny, C.L.; Servajean, G.; Hermosa, J.L.; Nesen, G. (Cuadernos de Geología Ibérica, 1981)
Sin resumen